Post-transcriptional regulation of lipoprotein receptors by the E3-ubiquitin ligase inducible degrader of the low-density lipoprotein receptor - Sorrentino, Vincenzo; Zelcer, Noam (Current opinion in lipidology, 2012)
The hepatic low-density lipoprotein receptor (LDLR) pathway is essential for clearing circulating LDL and is an important therapeutic target for treating cardiovascular disease. Abundance of the LDLR is subject to both transcriptional and nontranscriptional control. Here, we highlight a new post-transcriptional mechanism for controlling LDLR function via ubiquitination of the receptor by the E3-ubiquitin ligase inducible degrader of the LDLR (IDOL). IDOL is a recently identified transcriptional target of the liver X receptors. Acting as an E3-ubiquitin ligase IDOL promotes ubiquitination of the LDLR, thereby marking it for lysosomal degradation. The determinants required for degradation of the LDLR by IDOL have been largely identified. IDOL also targets two related lipoprotein receptors, the very low-density lipoprotein receptor and apolipoprotein E receptor 2. Despite several similarities, the IDOL, and PCSK9 pathways for controlling LDLR abundance seem independent of each other. Genome-wide association studies have recently identified IDOL as a locus influencing variability in circulating levels of LDL, thereby highlighting the possible role of IDOL in human lipoprotein metabolism. Transcriptional induction of IDOL by liver X receptor defines a new post-transcriptional pathway for controlling LDLR abundance and LDL uptake independent of sterol regulatory element binding proteins. Targeting IDOL activity may offer a novel therapeutic approach complementary to statins for treating cardiovascular disease.